(3bGfhf GdEOQGc aj JTQjM GdCadGcs - (3eMeO UGOb GdJfcGHfis; (3eMeO Hf GdMSf Hf Rjf GdOjf GdehShj GdYGedj , GHf GdTgjO GdKGfj,J (B1030 (3g` s ((3eMeO MSjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOhQfG dJTQjM GdCadGc CeG HYO , adG CbSe HGdTab aCKQJ Yde GdgjFI Cf CTQM QSGdI JTQjM GdCadGc s
(3BNQgG (B:s
(3gPG GdPi bO CYWGg VGYa Gddg HgGAg hdYdc HYO GdEMGWI HgPG , hSjeG EPG JQbjJ ef eHGMK GdbHdI Edi Pdc GdESJVGM hbO GSJQMJ dfbd gPG GdTQM ef GdShGO Edi GdHjGV s
(3HgG CTcGd hWjGQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B89 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B191s
Keywords: (3Gdadcs